Chapter José Ramón Mélida, traduttore del Lexique des termes d'art di Jules Adeline - Carpi, Elena (Lessico multilingue dei Beni Culturali, 2023)
The Vocabulario de Términos de Arte (Vocabulary of Art Terms) is the most important lexicographic work about art history published in Spain in the 19th century. Following his intention to spread knowledge about the lexis of art, José Ramón Mélida published this work after translating and adapting for the Spanish audience Jules Adeline's Lexique des terms d'art (Lexicon of art terms). This chapter employs descriptive-contrastive methodologies to analyse Mélida's translation strategies, his interventions on the source text as well as neologisms.